Use of Awake Flexible Fiberoptic Bronchoscopic Nasal Intubation in Secure Airway Management for Reconstructive Surgery in a Pediatric Patient with Burn Contracture of the Neck - Tolga Totoz; Kerem Erkalp; Sirin Taskin; Ummahan Dalkilinc; Aysin Selcan (Case Reports in Anesthesiology)
Although the use of awake flexible fiberoptic bronchoscopic (FFB) intubation is a well-recognized airway management technique in patients with difficult airway, its use in smaller children with burn contractures or in an uncooperative older child may be challenging. Herein, we report successful management of difficult airway in a 7-year-old boy with burn contracture of the neck, by application of FFB nasal intubation in a stepwise approach, first during an initial preoperative trial phase to increase patient cooperation and then during anesthesia induction for the reconstructive surgery planned for burn scars and contractures. Our findings emphasize the importance of a preplanned algorithm for airway control in secure airway management and feasibility of awake FFB intubation in a pediatric patient with burn contracture of the neck during anesthesia induction for reconstructive surgery. Application of FFB intubation based on a stepwise approach including a trial phase prior to operation day seemed to increase the chance of a successful intubation in our patient in terms of technical expertise and increased patient cooperation and tolerance by enabling familiarity with the procedure.